ANALISIS FAKTOR-FAKTOR YAN MEMPENGARUHI KINERJA REKSA DANA DI INDONESIA (Studi Empiris Pada Reksa Dana Konvensional di Indonesia Periode 2012-2014) - Bitomo, Habib; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2016)
Mutual funds are one alternative solution profitable investment for the investor. Beneficial because mutual funds managed by the investment manager to manage the fund in accordance with its investment objectives and does not require large capital. Investor needs to choose mutual funds in accordance with their capabilities and investment objectives because it will affect the return earned. This study was conducted to determine the effect of Past Performance, Fund Size, Age Fund, Expense Ratio, and Cash Flow of the Fund Mutual Fund Performance.The data used in this study are SBI, financial reports, prospectuses, and data NAV of 30 conventional mutual funds listed on the Stock Exchange 2012-2014. The sample was divided in accordance with the investment objectives of 10 Equity Funds, 10 Fixed Income Fund, and 10 Money Market Fund. This research using the Multiple Linear Regression.The test results showed that, overall, Past Performance, Fund Age, Expense Ratio, and Cash Flow Fund have a significant effect on the mutual fund performance, while the Fund Size do not affect the Mutual Fund Performance. The test results of the Equity Fund showed that Past Performance and Cash Flow have a significant effect on the Mutual Fund Performance, while the other variableÂ has no effect on the Mutual Fund Performance. The test results of the Fixed Income Fund showed that Fund Cash Flow have a significant effect on the Mutual Fund performance, while other variables have no effect on the Mutual Fund Performance. The test results of the Money Market FundÂ showed that Past Performance have a significant of the Mutual Fund performance, while other variables have no effect on the Mutual Fund Performance.